RESPONSES OF FUEL SUBSIDY REMOVAL AS SUSTAINABLE TRANSPORT POLICY (CASE STUDY: WORKERS IN JAKARTA) - Ariyanti, Octaviani; Sebhatu, Samuel Petros; Munthohar, Imam (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Motorization in urban areas contributes several problems such as congestion, accidents, gas emissions, noises, and infrastructure breakage. Meanwhile, most of the developing countries cannot overcome such growth activities, as well as in Jakarta. By December 2013, Vice Governor of Jakarta propose fuel subsidy removal policy as one of sustainable transport policy. This study is intended to understand and investigate how fuel subsidy removal policy scenarios (25%, 50%, and 100%) in Jakarta affects travellers’ behaviour and analyse such policy to support sustainable transport by using qualitative research methodology. Interviews and questionnaires survey are conducted to workers in Jakarta, which includes ranking scale question for traveller response options. The result shows that half of respondents are not affected and will only response to fuel price increasing at IDR 31.400 for gasoline price and IDR 26.300 for ADO (Auto Diesel Oil). Moreover, there is a tendency of respondent's to response by changing their travel mode choices into more fuel efficient private vehicle.